PEMAHAMAN TINDAK PIDANA TRANSAKSI ELEKTRONIK DALAM UNDANG-UNDANG NO 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Muhammad Junaidi; Kadi Sukarna; Bambang Sadono (LPPM ITB AAS Indonesia Surakarta, 2020)
Through the Understanding of the Crime of Electronic Transactions in Law No. 19 of 2016 concerning Electronic Information and Transactions, any inappropriate actions in carrying out electronic transaction activities are very important in ensuring legal certainty. Until now, there is no legal uncertainty regarding electronic transaction behavior which is a big problem in the process of national and state activities. Through service activities with dedication techniques providing a thorough understanding and indicators of service results in the form of a questionnaire, it is hoped that the implementation process of the service can provide the best benefits for the implementation of community service activities and the process of higher education tridharma. This can be an indicator of the implementation of service which is not just a formality but also contributes to the enforcement of justice for the community. Based on the results of the service, it was found that the participants' awareness of the situation appeared to be a problem in order to utilize the information technology used appropriately. However, such awareness certainly needs provisioning in the field of appropriate invitation regulations so that the existing understanding will appear comprehensive referring to Law No. 19 of 2016 concerning Electronic Information and Transactions. Through the Understanding of the Crime of Electronic Transactions in Law No. 19 of 2016 concerning Electronic Information and Transactions, any inappropriate actions in carrying out electronic transaction activities are very important in ensuring legal certainty. Until now, there is no legal uncertainty regarding electronic transaction behavior which is a big problem in the process of national and state activities. Through service activities with dedication techniques providing a thorough understanding and indicators of service results in the form of a questionnaire, it is hoped that the implementation process of the service can provide the best benefits for the implementation of community service activities and the process of higher education tridharma. This can be an indicator of the implementation of service which is not just a formality but also contributes to the enforcement of justice for the community. Based on the results of the service, it was found that the participants' awareness of the situation appeared to be a problem in order to utilize the information technology used appropriately. However, such awareness certainly needs provisioning in the field of appropriate invitation regulations so that the existing understanding will appear comprehensive referring to Law No. 19 of 2016 concerning Electronic Information and Transactions. Keywords: Understanding, criminal acts, and electronic transactions